Effect of annealing temperatures on the structural and optical properties of indium tin oxide (ITO) thin films grown on glass substrate - Siti Norshaza Shahira, Rosli (2016)
Metallic oxides are one of the transparent semiconductors that having abundant application in industry. Indium tin oxide (ITO) is an example of metallic oxide which commonly referred to ITO thin films. ITO were prepared by sol-gel method which coated on the glass substrate and then annealed in the various temperatures of in the range 300 to 500 ℃ in order to improve their structural and optical properties. In this study, the characterization techniques of X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), UV-visible (UV-Vis), and photoluminescence (PL) spectra measurements were performed to investigate the effects of substrate on the structural and optical properties of ITO thin films. For structural properties, the XRD results indicated that the highest intensity peak for the highest annealed treatment, 500 ℃ ITO thin film is (222) while for the lowest annealed treatment, 300 ℃ have no peaks appeared at all. While FESEM characterization showed the grain size ITO thin films for the highest annealing temperature, 500 ℃ is bigger compared to the grain size of ITO thin films annealed at 300 ℃. For optical characteristics, UV-Vis analysis shows the band gap plotted from the Tauc’s plot give that the energy band gap of each samples are from 4.1 eV to 4.5 eV. For Photoluminescence spectroscopy, it can be evidently seen that for all ITO films samples, there is an UV emission peak at approximately 535 nm and 585 nm.